Dual Efficacy of Delta Opioid Receptor-Selective Ligands for Ethanol Drinking and Anxiety - van Rijn, Richard M. (The American Society for Pharmacology and Experimental Therapeutics, 2010)
Alcoholism and anxiety disorders have a huge impact on society and afflict 17.6 million and 40 million people in the United States, respectively. A strong comorbidity exists between alcoholism and anxiety disorders. Indeed, alcohol withdrawal-induced anxiety is a primary contributing factor for relapse, and anxiolytics are a common adjuvant therapy prescribed for treatment-seeking alcoholics. It is thought that the use of alcohol to self-medicate and relieve anxiety contributes to the development of addiction. Treatment for anxiety disorders and alcoholism exist but are not universally effective. The delta opioid receptor (DOR) plays a role in both alcohol consumption and anxiety, making it a very interesting clinical target. Two pharmacologically distinct DORs have been described: DOR1 and DOR2. We find here that the relative specificity of DOR agonists for DOR1 or DOR2 can greatly affect the effects they exert on ethanol consumption and anxiety. The DOR1 agonist 2-methyl-4aα-(3-hydroxyphenyl)-1,2,3,4,4a,5,12,12aα-octahydro-quinolino[2,3,30g]isoquinoline (TAN-67), although not effective in decreasing anxiety-like behavior in naive mice, has anxiolytic-like properties in ethanol-withdrawn mice. In contrast, a less subtype-selective agonist, (+)-4-[(αR)-α-((2S,5R)-4-allyl-2,5-dimethyl-1-piperazinyl)-3-methoxybenzyl]-N,N-diethylbenzamide (SNC80), while also reducing anxiety-like behavior, increases ethanol consumption. In addition, we found that the conical anxiolytic diazepam [DZ; 7-chloro-1-methyl-5-phenyl-3H-1,4-benzodiazepin-2(1H)-one] is a less effective anxiolytic in ethanol-withdrawn mice than in naive mice. Together, our findings suggest that selective DOR agonists can decrease anxiety-like behavior and are more effective than diazepam at reducing ethanol consumption. We believe the dual efficacy of DOR1 agonists makes these receptors an interesting therapeutic target for treatment-seeking alcoholics.